The Effect of Total Cholesterol Variability on Clinical Outcomes After Percutaneous Coronary Intervention - Liang, Yanting; Wang, Haochen; Liu, Fengyao; Yu, Xueju; Liang, Yan; Yin, Han; Liu, Yuting; Jiang, Cheng; Wang, Yu; Bai, Bingqing; Liu, Anbang; Shi, Xiaohe; et al. (Frontiers in Public Health, 2022)
Aim Exploring the risk factors of prognosis in patients undergoing percutaneous coronary intervention (PCI) is of great importance. Our aim of the study is to investigate the association between variability in total cholesterol (TC) level and major adverse cardiovascular and cerebrovascular events (MACCE) in patients after PCI. Methods Between April 2004 and December 2009, 909 patients who underwent primary PCI and with at least three TC values were included in the final study. TC variability was calculated using four indices: standard deviation (SD), coefficient of variation (CV), the average successive variability (ASV), variability independent of the mean (VIM). MACCE comprised all-cause mortality, non-fatal myocardial infarction (MI), unplanned revascularization, hospitalization for heart failure, and non-fatal stroke. Results There were 394 cases of MACCE during the follow-up period. When the subjects were divided into quartile groups by CV of TC, high CV groups were associated with a higher hazard ratio of MACCE than for lower CV groups. In multivariable adjusted models, TC variability and MACCE remained correlated [HR (95% CI): Q2, 1.17 (0.86–1.58); Q3, 1.38 (1.03–1.85); Q4, 1.63 (1.22–2.17)]. Similar patterns of MACCE were noted by quartiles of SD, ASV, and VIM. Conclusion Visit-to-visit TC variability is positively correlated with MACCE in patients after PCI.